2001
DOI: 10.1093/biolreprod/65.4.1215
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Bisphenol A Alters the Development and Tissue Organization of the Mouse Mammary Gland1

Abstract: Exposure to estrogens throughout a woman's life, including the period of intrauterine development, is a risk factor for the development of breast cancer. The increased incidence of breast cancer noted during the last 50 years may have been caused, in part, by exposure of women to estrogen-mimicking chemicals that are released into the environment. Here, we investigated the effects of fetal exposure to one such chemical, bisphenol A (BPA), on development of the mammary gland. CD-1 mice were exposed in utero to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
261
1
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 358 publications
(278 citation statements)
references
References 49 publications
10
261
1
6
Order By: Relevance
“…At 4 months of age, these animals had a significant increase in lateral branching [30]. By 6 months of age, we observed an overall increase in epithelial structures including terminal ends and a premature appearance of alveolar buds, normally associated with pregnancy in the mouse [31]. More importantly, BPA exposed mice that were ovariectomized prepubertally showed an enhanced sensitivity to estradiol demonstrated by an increase in the number of TEBs, TEB area, TEB density and ductal extension [30,32].…”
Section: Introductionmentioning
confidence: 89%
“…At 4 months of age, these animals had a significant increase in lateral branching [30]. By 6 months of age, we observed an overall increase in epithelial structures including terminal ends and a premature appearance of alveolar buds, normally associated with pregnancy in the mouse [31]. More importantly, BPA exposed mice that were ovariectomized prepubertally showed an enhanced sensitivity to estradiol demonstrated by an increase in the number of TEBs, TEB area, TEB density and ductal extension [30,32].…”
Section: Introductionmentioning
confidence: 89%
“…BPA binds to estrogen receptors α and β (13) and to membranebound estrogen receptors (14) and, thus, affects various functions at all levels of biological complexity in estrogen target organs (15)(16)(17)(18)(19)(20)(21). Animal studies showed that BPA exposure at or below the reference dose of 50 μg/kg per day (http://cfpub.epa.gov/ncea/iris/index.…”
mentioning
confidence: 99%
“…More importantly, BPA exposure during gestation and organogenesis produces effects that alter the structure and function of target organs (24). In particular, these low environmentally relevant developmental exposures caused changes in the tissue organization of the mouse mammary gland observed during fetal development (25), and further changes manifested long after the end of exposure at puberty (18,26) and in adulthood (18,(26)(27)(28)(29)(30). Female mice exposed to BPA during gestation also displayed a heightened response to estrogen compared with unexposed controls (31) and developed intraductal hyperplasias, i.e., a precancerous lesion (28).…”
mentioning
confidence: 99%
“…Invasive cancers were observed in those animals exposed to low doses of BPA when they were further challenged by a sub-carcinogenic dose of the chemical carcinogen N-nitroso-N-methylurea at puberty (Durando et al, 2007). BPA was also reported to increase the number of terminal end buds lateral branching and epithelial density, the presence of secretory products within the alveoli and increased stromal cell nuclear density (Markey et al, 2001;Munoz-de-Toro et al, 2005;Durando et al, 2007). Furthermore, BPA has been shown to cross the placenta in rodents and increase the bioavailability of estrogens at the fetal circulation (Richter et al, 2007).…”
Section: Bisphenol a (Bpa)mentioning
confidence: 97%